Solamargine Inhibits the Development of Hypopharyngeal Squamous Cell Carcinoma by Decreasing LncRNA HOXA11-As Expression - Meng, Ying; Jin, Mengli; Yuan, Dai; Zhao, Yicheng; Kong, Xiangri; Guo, Xuerui; Wang, Xingye; Hou, Juan; Wang, Bingmei; Song, Wu; Tang, Yong (Frontiers in Pharmacology, 2022)
Hypopharyngeal squamous cell carcinoma (HSCC) is one of the high mortality cancers with poor prognosis, which is driving the development of new chemotherapeutic agents. Herein, we identified the anticancer effects of a natural compound, solamargine (SM), on FaDU cells and explored its mechanism in terms of non-coding RNA. It was observed that SM inhibited the proliferation of FaDU cells with an IC50 of 5.17 μM. High-throughput sequencing data revealed that lncRNA HOXA11-AS was significantly down-regulated in cells co-incubated with SM. Further assays demonstrated that SM-induced down-regulation of lncRNA HOXA11-AS showed important implications for apoptosis. Given the properties of HOXA11-AS as miR-155 sponge, we further confirmed that SM up-regulated the expression of miR-155 in FaDU cells. C-Myc, a transcription factor that regulates cell differentiation and apoptosis, whose mRNA is considered to be targeted by miR-155. We showed that c-Myc expression was down-regulated by SM and accompanied by increased apoptosis, which was consistent with the findings of transcriptome sequencing. Furthermore, SM administration suppressed xenograft tumor growth in a xenograft mouse model in vivo. In the light of the above, our results suggested that SM downregulated the expression of HOXA11-AS, which in turn induces apoptosis by downregulating c-Myc in FaDU, providing evidence for the anticancer effect of SM on HSCC and uncovering the effect of SM on non-coding RNAs is, at least partly, a mechanism of action.